2017
DOI: 10.1002/acp.3347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feedback on Self‐Evaluations and Self‐Regulation in Elementary School

Abstract: Elementary school learners are typically highly confident when judging accuracy of their test responses, relatively independent of whether these are correct. While feedback has been shown to improve accuracy of adults' and adolescents' selfevaluations and subsequent self-regulation, little is known about beneficial effects for elementary school children. We investigated effects of fine-grained feedback on fourth and sixth graders' self-evaluations and restudy selections by presenting them the ideas they were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 64 publications
(109 reference statements)
0
34
0
Order By: Relevance
“…Some researchers have shown that providing performance feedback is an operant way to reduce overconfidence (e.g., Arkes et al, 1987 ; O’Connor, 1989 ; van Loon and Roebers, 2017 ), whereas others did not find this positive effect of feedback (e.g., Subbotin, 1996 ; Pulford and Colman, 1997 ; Zamary et al, 2016 ). Stone and Opel (2000) found different effects of various types of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that providing performance feedback is an operant way to reduce overconfidence (e.g., Arkes et al, 1987 ; O’Connor, 1989 ; van Loon and Roebers, 2017 ), whereas others did not find this positive effect of feedback (e.g., Subbotin, 1996 ; Pulford and Colman, 1997 ; Zamary et al, 2016 ). Stone and Opel (2000) found different effects of various types of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…As regulation judgments directly influence whether and how students continue learning and indirectly influence whether they will master the learning goals or not, making accurate regulation judgments is important. We use the concept "regulation accuracy" to indicate the extent to which the regulation judgments are in line with students' actual need for regulation, as indicated by experts (thus actual regulation actions were not measured, which is in line with prior studies; e.g., Baars et al, 2014;Van Loon & Roebers, 2017). Making accurate regulation judgments appears to be a skill that is strongly under development during the upper years of primary school: Studies about primary school students practicing recall (of word-pairs or information from a video) showed that regulation judgments of fifth graders are influenced more strongly by their monitoring judgments than those of third graders and were also far more accurate (i.e., unknown words or definitions were more often selected for restudy).…”
Section: Monitoring and Regulation Judgmentsmentioning
confidence: 96%
“…Two central processes in most models of self-regulated learning, and in switching between the processes, are self-monitoring (evaluating one's own performance) and self-regulation (controlling one's own study activities; De Bruin & Van Gog, 2012;Panadero, 2017;Griffin et al, 2013). Unfortunately, primary school students' self-monitoring and self-regulation are often inaccurate, and researchers are looking for ways to help them improve these processes (e.g., Baars et al, 2014;García et al, 2016;Van Loon & Roebers, 2017). However, relatively little attention has been paid to self-monitoring, and especially self-regulation, when practicing with problem-solving tasks (van Gog et al, 2020), even though problem solving plays an important role in many primary and secondary school subjects such as mathematics and science (for exceptions, see Baars et al, 2014Baars et al, , 2018Boekaerts & Rozendaal, 2010;García et al, 2016;Rutherford, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In selfregulated learning model, the sub-processes of monitoring and self-evaluation are related to self-assessment (Zimmerman, 2000). Students' self-assessment practices in the classrooms increase their interest and motivation, support them to be more proficient in their own works, promote their self-regulated learning (Oscarson, 2013;van Loon and Roebers, 2017;Vasu et al, 2020), and improve their academic success (Desoete, Roeyers, & Buysse, 2001;Sharma et al, 2016;Winne, 2005;Zimmerman, 2008). Thus, students will be more proactive learners with accurate self-assessment (Boud, 2013).…”
Section: Introductionmentioning
confidence: 99%